2011
DOI: 10.1016/j.homp.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of homeopathic care through objective and shared indicators

Abstract: This paper demonstrates a new methodological approach to assess the effectiveness of a therapeutic modality, without ad-hoc clinical trials. This methodology can be used by public health institutions in which non-conventional medicines are integrated into the public health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Among the more controversial papers in this issue is that from Maria Francesca Romano's team at the University of Pisa. 10 They propose a new method for measuring the effectiveness of Homeopathy using standard care indicators collected by the public health authorities. They compare patients receiving Homeopathy with the general population in the same region in terms of drug use and hospitalisation indicators.…”
Section: The Community Perspectivementioning
confidence: 99%
“…Among the more controversial papers in this issue is that from Maria Francesca Romano's team at the University of Pisa. 10 They propose a new method for measuring the effectiveness of Homeopathy using standard care indicators collected by the public health authorities. They compare patients receiving Homeopathy with the general population in the same region in terms of drug use and hospitalisation indicators.…”
Section: The Community Perspectivementioning
confidence: 99%
“…Most Unani drugs are safe, but toxicity, including liver injury, has also been observed [5,6]. Furthermore, there are very few scientific attempts to certify and validate the safety of Unani's drugs [7,8]. Therefore, the numerous studies reported have evaluated the hepatoprotective and antioxidant potential of many Unani drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Most Unani drugs are safe, but toxicity including liver injury has also been observed (Licata et al, 2013;Oberbaum et al, 2012). Moreover, there are very few scientific attempts attesting and validating the safety of Unani drugs (Leone et al, 2011;Rutten, 2011). Therefore, the present study evaluates the hepatoprotective and antioxidative potential of a Unani medicine, known as Habb-e-Asgand.…”
Section: Introductionmentioning
confidence: 99%